DIFFERENCES IN PHYSICAL ACTIVITY OF FEMALE STUDENTS IN THE FIRST YEAR OF THE FACULTY OF KINESIOLOGY AND THE FACULTY OF ECONOMICS - Anđelko Šimić, (Sport Scientific And Practical Aspects, 2025)
Hypokinesia is one of the main threats to the preservation of human health and the fight against it helps to preserve our entire population. Accordingly, it should be pointed out that the most suitable for raising awareness in society of the necessity of physical activity are educated experts in the field of education and health. The aim of this paper is to determine the differences in physical activity between first – year female students of the Faculty of Kinesiology in Osijek and first – year female students of the Faculty of Economics in Osijek by using the International Physical Activity Questionnaire (IPAQ). The research was conducted on a sample of a 133 respondents, 15 first – year female students of the Faculty of Kinesiology and 118 first year female students of the Faculty of Economics of Josip Juraj Strossmayer University in Osijek. International physical activity questionnaires (IPAQ) were distributed to the participants when they arrived in the hall. The questionnaires contain a part with general data: name of the faculty, chronological age and gender of the respondents. A multivariate analysis of variance MANOVA of different groups was used to determine the differences between the applied physical activity assessment tests (IPAQ) between groups of subjects classified by college attended. Expectations were confirmed about the difference manifested in the variable Total average physical activity (PATA), where female students of the first year of the Faculty of Kinesiology have statistically significantly higher values compared to female students of the first year of the Faculty of Economics.